Molecular Recognition and Scavenging of Arsenate from Aqueous Solution Using Dimetallic Receptors. Issue 51 (22nd October 2014) - Moffat, Chris D.; Weiss, Dominik J.; Shivalingam, Arun; White, Andrew J. P.; Salaün, Pascal; Vilar, Ramon
Abstract A series of copper(II), nickel(II) and zinc(II) dimetallic complexes were prepared and their affinities towards arsenate investigated. Indicator displacement assays (IDAs) were carried out to establish the complexes with best affinities towards arsenate. A di‐zinc complex (3) was selected and its arsenate‐binding abilities investigated by isothermal titration calorimetry (ITC). The X‐ray crystal structure of this metallo‐receptor bound to arsenate is also reported, which allowed us to establish the binding mode between 3 and this oxyanion. Immobilising 3 onto HypoGel resin yielded a novel adsorbent (Zn–HypoGel) with high affinity for arsenate. Adsorption of arsenate from competitive solutions and natural groundwater was greater than that of the commercially used iron oxide Bayoxide E33. Zn–HypoGel could be efficiently and simply regenerated by washing with sodium acetate solution.